PENERAPAN GREEN ACCOUNTING DAN MATERIAL FLOW COST ACCOUNTING TERHADAP SUSTAINABLE DEVELOPMENT - Dina Khairuna Siregar; Ria Hindriani; Riyanthi Idayu; Mohamad Husni (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
The aim of this research is to analyze the application of Green Accounting and Material Flow Cost Accounting to Sustainable Development. The research method uses quantitative descriptive methods. The population in this study was 89 basic industry and chemical sector companies registered on the IDX for the 2018-2022 period and the total sample obtained was 15 companies. The research sample was taken using a purposive sampling method and the data source used was secondary data in the form of the company's annual financial report. Data analysis techniques use descriptive statistical tests, t tests and F tests using SPSS 25. The results of this research partially prove that the implementation of Green Accounting has no effect on Sustainable Development. This happens because companies have not fully implemented green accounting practices consistently in their business operations so that it does not affect Sustainable Development. Apart from that, the results of this research also prove that the application of Material Flow Cost Accounting has an effect on sustainable development. This happens if the company carries out MFCA, the company can manage costs and achieve efficiency and reduce production waste so that company profits increase, thus influencing sustainable development. And simultaneously, this research proves that Green Accounting and Material Flow Cost Accounting have an effect on Sustainable Development